2017
DOI: 10.3389/fpls.2017.02108
|View full text |Cite
|
Sign up to set email alerts
|

OsJAZ1 Attenuates Drought Resistance by Regulating JA and ABA Signaling in Rice

Abstract: Jasmonates (JAs) and abscisic acid (ABA) are phytohormones known play important roles in plant response and adaptation to various abiotic stresses including salinity, drought, wounding, and cold. JAZ (JASMONATE ZIM-domain) proteins have been reported to play negative roles in JA signaling. However, direct evidence is still lacking that JAZ proteins regulate drought resistance. In this study, OsJAZ1 was investigated for its role in drought resistance in rice. Expression of OsJAZ1 was strongly responsive to JA t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
96
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 149 publications
(115 citation statements)
references
References 62 publications
7
96
0
Order By: Relevance
“…Jasmonate ZIM-domain proteins (JAZ) are regulators, typically repressors, in the JA signaling pathway. Fu et al [33] demonstrated that OsJAZ1 plays a negative regulatory role in rice drought stress tolerance, particularly in relation to the ABA and JA signaling pathways. In addition, Seo et al [18] found that OsbHLH148, a basic helix-loop-helix protein, acts as a transcriptional regulator and up regulates OsDREB1 and OsJAZ, which are involved in drought stress responses and the JA signaling pathway, respectively.…”
Section: Drought Stressmentioning
confidence: 99%
“…Jasmonate ZIM-domain proteins (JAZ) are regulators, typically repressors, in the JA signaling pathway. Fu et al [33] demonstrated that OsJAZ1 plays a negative regulatory role in rice drought stress tolerance, particularly in relation to the ABA and JA signaling pathways. In addition, Seo et al [18] found that OsbHLH148, a basic helix-loop-helix protein, acts as a transcriptional regulator and up regulates OsDREB1 and OsJAZ, which are involved in drought stress responses and the JA signaling pathway, respectively.…”
Section: Drought Stressmentioning
confidence: 99%
“…The increase in the endogenous JA content was rapid and transient in A. thaliana [21] and citrus (Citrus paradisi × Poncirus trifoliata) [115] immediately after drought stress, but the content decreased to the basal level with prolongation of the stress. MeJA treatment could improve the drought resistance in peanut (Arachis hypogaea) [116], rice (Oryza sativa) [117], soybean (Glycine max) [118], and broccoli (Brassica oleracea) plants [119]. The application of exogenous MeJA not only increased the total carbohydrate, polysaccharide, total soluble sugar, free amino acid, total proline, and protein contents, but also the activities of catalase (CAT), POD, and SOD in maize plants (Zea mays) [120].…”
Section: Jasmonic Acid Signaling Under Drought Stressmentioning
confidence: 99%
“…The result is consistent with the data showing that JAZ1 is involved in the crosstalk between the JA and ABA signaling pathways though JAZ1-PYL interactions. The expression of OsJAZ1 not only responds to JA but also induced by ABA (Fu et al, 2017). The different ABA responses of JAZ1 and OsJAZ1 may be derived from their species.…”
Section: Jaz1-pyl4 and Jaz1-abi1 Interactions Mediate Cross Talk Bementioning
confidence: 99%
“…A reasonable hypothesis is that ABA and JA co-regulate plant growth and development and that JAZ1 is involved in this process. In addition, these interactions may explain the JA-hypersensitive phenotype of pyl4 mutant and the ABA-hypersensitive phenotype of osjaz1 mutant (Fu et al, 2017;Lackman et al, 2011).…”
Section: Confirmation Of the Interactions Of Two Proteins With Jaz1mentioning
confidence: 99%
See 1 more Smart Citation